PERAN INSTITUSI PENDIDIKAN DALAM PENGEMBANGAN NILAINILAI MORAL MELALUI SIKAP ILMIAH (SCIENTIFIC ATTITUDE) - Kartika Nur Fathiyah Fathiyah (Paradigma, 2006)
Many complaints uttered concerning with the low ethics of students in the educational process, such as cheating in exams, data manipulation, plagiarism, and the phenomena of ‘jockeying’ (cheating in exams by taking the exam for the benefit of somebody else). These divergences need to be responded by always empowering all components involved in the educational institutions to hold high the scientific attitudes in every process of education.Scientific attitudes is firstly hold up by always motivating all componentsinvolved in educational institutions to develop and satisfy the curiositywhich is naturally a basic trait of human beings. This curiosity will lead tofundamental scientific attitudes such as being honest in recording factualdata, perseverant in accomplishing tasks, open to scientific truth, andalways putting first priority to the truth obtained by means of scientificmethod, critical in responding to every proposition, statement or opinion,and creative while carrying out an experiment or research. Besides, theindividual will always be consistent to use logic and reasoning in understanding and solving his/her problems. The responsibility coming inline with satisfying this curiosity will make the individual put aside all thedishonest and deceitful attitudes.That is why educational institutions are hoped to be the main sources offacilities for individuals to satisfy their curiosity, and to provide democratic, open, non-authoritarian and supporting educational atmosphere for individuals to perform scientific activities such asobservation, experiment, and research. Also, educational institutions areexpected to play an important role as a medium for reinforcement of thegrowth of academic attitudes as well as an agent of socialization for thecommunity to generate academic attitudes, so that the community willeventually feel responsible to hold upright scientific attitudes.Key words : educational institution, value development, academic attitudes